2018
DOI: 10.1158/1078-0432.ccr-18-0573
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Responses to TP53 “Hotspot” Mutations and Unique Neoantigens Expressed by Human Ovarian Cancers

Abstract: COUNTS Statement of Translational RelevanceThis study demonstrated that T cells with specificity to mutated neoantigens were present in tumor infiltrating lymphocytes in patients with metastatic ovarian cancer, sometimes at high frequencies and with multivalent reactivity, suggesting that these T cells could be used for adoptive cell therapy. Furthermore, T cells from two of the patients were specific for TP53 "hotspot" mutations (c.659A>G; p.Y220C and c.733G>A; p.G245S), which are also expressed in a broad ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 47 publications
0
116
0
Order By: Relevance
“…Hemotoxylin and eosin staining of HGSOC tumors from these three individuals were attached in . Although no targeted therapies are yet available for these TP53 mutations, in a recent study, tumor infiltrating T‐cell responses to two TP53 hotspot mutations G245S and Y220C were identified in the context of HLA‐DRB3*02:02 in two separate ovarian cancer patients . Among the tumors sequenced in this cohort, five harbored the TP53 Y220C mutation and one had the G245S mutation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hemotoxylin and eosin staining of HGSOC tumors from these three individuals were attached in . Although no targeted therapies are yet available for these TP53 mutations, in a recent study, tumor infiltrating T‐cell responses to two TP53 hotspot mutations G245S and Y220C were identified in the context of HLA‐DRB3*02:02 in two separate ovarian cancer patients . Among the tumors sequenced in this cohort, five harbored the TP53 Y220C mutation and one had the G245S mutation.…”
Section: Discussionmentioning
confidence: 80%
“…Although no targeted therapies are yet available for these TP53 mutations, in a recent study, tumor infiltrating T-cell responses to two TP53 hotspot mutations G245S and Y220C were identified in the context of HLA-DRB3*02:02 in two separate ovarian cancer patients. 20 Among the tumors sequenced in this cohort, five harbored the TP53 Y220C mutation and one had the G245S mutation. Although HLA typing was not performed for this cohort, HLA-DRB3*02:02 had over 22% population frequency among the Chinese population in the US.…”
Section: Discussionmentioning
confidence: 89%
“…Although previously thought to be rare, the number of identified public neoantigens has rapidly increased in recent years. These include public neoantigens associated with common driver oncogenes, such as KRAS, BRAF, beta‐catenin, CDK4, H3.3K27M, and IDH1 as well as tumor suppressor genes, like TP53 . Whether immunogenic epitopes can be discovered for the 119 other known driver oncogenes remains an area of active investigation.…”
Section: Clinical Experience With Tcr‐based Cancer Immunotherapiesmentioning
confidence: 99%
“…These include public neoantigens associated with common driver oncogenes, such as KRAS, 11,18,206,207 BRAF, 170 beta-catenin, 198 CDK4, 208,209 H3.3K27M, 210 and IDH1 211 as well as tumor suppressor genes, like TP53. 212,213 Whether immunogenic epitopes can be discovered for the 119 other known driver oncogenes 214 have provided in vivo evidence that infusion of public neoantigenspecific T cells can be associated with durable cancer regression in humans. 11,170 Notwithstanding these exciting findings, it remains the case that most cancer neoantigens are privately held by individual patients.…”
Section: Public and Private Cancer Neoantigensmentioning
confidence: 99%
“…Neoantigen-specific T cells can be identified in patients not only with melanoma, but also with epithelial cancers, such as lung cancer [119,120], gastrointestinal cancer [121][122][123], ovarian cancer [124][125][126], breast cancer [127] and pancreatic cancer [128]. Case reports have demonstrated that treatment of the gastrointestinal and breast cancer patients with a T cell population highly enriched in neoepitope-specific T cells caused tumour regression [121,123,127].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%